Effects of lactoferrin and lactoperoxidase‐containing food on the oral hygiene status of older individuals: A randomized, double blinded, placebo‐controlled clinical trial. Issue 5 (6th May 2016) - Morita, Yu; Ishikawa, Kentaro; Nakano, Manabu; Wakabayashi, Hiroyuki; Yamauchi, Koji; Abe, Fumiaki; Ooka, Takafumi; Hironaka, Shouji
Abstract: Aim: Lactoferrin and lactoperoxidase have antimicrobial effects against oral pathogens. This randomized, double‐blinded, placebo‐controlled parallel group study tested the efficacy of a lactoferrin and lactoperoxidase‐containing tablet (LF + LPO tablet) in improving the oral hygiene status of older individuals. Methods: A total of 46 participants (31 nursing home residents and 15 healthy older individuals) were randomly assigned to receive either lactoferrin and lactoperoxidase‐containing tablets or placebo tablets, and were asked to suck on a tablet after every meal for 8 weeks. Oral and bacteriological assessments were carried out at baseline, 4 weeks and 8 weeks. Results: A total of 47 participants (test group n  = 20; mean age 80.4 ± 6.4 years; placebo group n  = 17; mean age 85.9 ± 6.7 years) were included in the efficacy analysis. In the test group, the total number of bacteria in the tongue coating was significantly reduced at 4 and 8 weeks compared with that at baseline, and the number of Porphyromonas gingivalis and Fusobacterium nucleatum was significantly reduced at 8 weeks. The total number of bacteria and the number of P. gingivalis in the supragingival plaque were significantly reduced at 8 weeks. Furthermore, there was a significant difference in the change in the number of P. gingivalis in supragingival plaque at 8 weeks between the two groups. Conclusions: Lactoferrin and lactoperoxidase‐containing tablet ingestion showed antibacterial effects on periodontal bacteria present in the tongue coating and supragingival plaque, indicating that long‐term ingestion could improve the oral hygiene of older individuals.Geriatr Gerontol Int 2017; 17: 714–721.